Respuesta :

Answer:

see explanation

Step-by-step explanation:

If (x - 1) is a factor then f(1) = 0

Given

f(x) = x³ - 13x² + 32x - 20 , then

f(1) = 1³ - 13(1)² + 32(1) - 20

     = 1 - 13 + 32 - 20

     = 0

Since f(1) = 0 then (x - 1) is a factor

Using Synthetic division

 1  | 1  - 13   32   - 20

      ↓    1   - 12      20    

     -----------------------------

      1    - 12   20     0 ← remainder

quotient = x² - 12x + 20 = (x - 2)(x - 10)

Then

x³ - 13x² + 32x - 20 = (x - 1)(x - 2)(x - 10) ← in factored form